2016
DOI: 10.1038/srep34434
|View full text |Cite
|
Sign up to set email alerts
|

Temporal dynamics of hot desert microbial communities reveal structural and functional responses to water input

Abstract: The temporal dynamics of desert soil microbial communities are poorly understood. Given the implications for ecosystem functioning under a global change scenario, a better understanding of desert microbial community stability is crucial. Here, we sampled soils in the central Namib Desert on sixteen different occasions over a one-year period. Using Illumina-based amplicon sequencing of the 16S rRNA gene, we found that α-diversity (richness) was more variable at a given sampling date (spatial variability) than o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
66
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(83 citation statements)
references
References 66 publications
5
66
2
Order By: Relevance
“…Our analysis, using an unprecedented sequencing depth for these types of communities, revealed a similar microbial community structure across substrates at the phylum level, which is consistent with previous studies of endolithic communities from multiple deserts (de la Torre et al , 2003; Walker et al , 2005; Dong et al , 2007; Pointing et al , 2007; Azúa-Bustos et al , 2011; DiRuggiero et al , 2013; Li et al , 2013; Crits-Christoph et al , 2016; Armstrong et al , 2016; Lee et al , 2016; Archer et al , 2017; Lacap-Bugler et al , 2017) and suggests that these phyla constitute an ubiquitous “metacommunity” available for the colonization of lithobiontic substrates (Walker and Pace 2007). Indeed, the most abundant taxa at the OTU level all belonged to genera recognized for their resistance to desiccation, radiation, and oligotrophic conditions found in hyper-arid deserts (Friedmann and Ocampo-Friedmann 1995; Potts 1999; Billi et al , 2000; Bull 2011; Krisko and Radman 2013; Mohammadipanah and Wink 2016; Lebre et al , 2017).…”
Section: Discussionsupporting
confidence: 89%
“…Our analysis, using an unprecedented sequencing depth for these types of communities, revealed a similar microbial community structure across substrates at the phylum level, which is consistent with previous studies of endolithic communities from multiple deserts (de la Torre et al , 2003; Walker et al , 2005; Dong et al , 2007; Pointing et al , 2007; Azúa-Bustos et al , 2011; DiRuggiero et al , 2013; Li et al , 2013; Crits-Christoph et al , 2016; Armstrong et al , 2016; Lee et al , 2016; Archer et al , 2017; Lacap-Bugler et al , 2017) and suggests that these phyla constitute an ubiquitous “metacommunity” available for the colonization of lithobiontic substrates (Walker and Pace 2007). Indeed, the most abundant taxa at the OTU level all belonged to genera recognized for their resistance to desiccation, radiation, and oligotrophic conditions found in hyper-arid deserts (Friedmann and Ocampo-Friedmann 1995; Potts 1999; Billi et al , 2000; Bull 2011; Krisko and Radman 2013; Mohammadipanah and Wink 2016; Lebre et al , 2017).…”
Section: Discussionsupporting
confidence: 89%
“…Nutrient stratification in surface and subsurface soils was not observed (Fig. 2B,C ; Table 1 ) 14 which confirmed that nutrient cycling is very limited in Namib Desert soils 31 . Edaphic and hypolithic C and N chemistries were also found to be independent of the year of sampling (Table 1 ), most probably reflecting their local and long-term “hydro-histories” 32 , 33 .…”
Section: Discussionmentioning
confidence: 55%
“…This study could have benefited from the monitoring of the bulk soil community throughout the experiment (i.e., sampled in parallel with rhizosphere sampling time points), as the bulk soil microbial composition can vary significantly over short timescales ( Li et al, 2014b ). However, some studies have shown that the microbial community varies less over time in comparison to other factors, such as spatial comparisons ( Armstrong et al, 2016 ). Similarly, Shade et al (2013) reported that soil microbial communities show little change over short/moderate time periods (<6 months).…”
Section: Discussionmentioning
confidence: 99%